2015
DOI: 10.1136/thoraxjnl-2014-206578
|View full text |Cite
|
Sign up to set email alerts
|

Lung structure-function correlation in patients with primary ciliary dyskinesia

Abstract: We demonstrated that measuring LCI in patients with PCD is of clinical relevance; it was more frequently abnormal than FEV1, correlated well with CFCT and was more sensitive than FEV1 to detect patients with structural abnormalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
118
2
7

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(138 citation statements)
references
References 31 publications
12
118
2
7
Order By: Relevance
“…Also, spirometry (forced vital capacity, forced expiratory volume in 1 s and forced expiratory flow at 25-75% of FVC) was used to measure lung function, but spirometry measures mainly proximal obstruction. Patients with PCD, like those with CF, primarily have peripheral airway obstruction that is picked up much better by gas washout techniques [14][15][16]. 4) Although the study nearly reached the target sample size, it was underpowered mainly because observed variability of the outcomes was larger than anticipated.…”
Section: What the Study Foundmentioning
confidence: 99%
“…Also, spirometry (forced vital capacity, forced expiratory volume in 1 s and forced expiratory flow at 25-75% of FVC) was used to measure lung function, but spirometry measures mainly proximal obstruction. Patients with PCD, like those with CF, primarily have peripheral airway obstruction that is picked up much better by gas washout techniques [14][15][16]. 4) Although the study nearly reached the target sample size, it was underpowered mainly because observed variability of the outcomes was larger than anticipated.…”
Section: What the Study Foundmentioning
confidence: 99%
“…Lung clearance index (LCI) derived from multiple breath washout is a radiation-free candidate for disease monitoring and seems to be particularly sensitive for detecting early lung disease compared to FEV1 [59]. However, correlations between LCI and HRCT have also shown opposing results, and longitudinal data are lacking [58,60].…”
Section: Lower Airway Managementmentioning
confidence: 99%
“…Radiation risks need to be balanced against the benefits of identifying early airway changes, but the data on which to base the assessments are limited. Correlations between bronchiectasis severity scores derived from HRCT and FEV1 have produced conflicting results [56][57][58]. Future studies must avoid selection bias, as patients who have routine imaging tests tend to have more severe disease.…”
Section: Lower Airway Managementmentioning
confidence: 99%
“…A close relationship among infection, inflammation, lung function, and imaging suggests a real association between measures (2), a necessary point considering the possibility of therapeutic interventions. Such a structure-function relationship between multiple-breath washout (MBW) and computed tomography (CT) scans has already been demonstrated in older children and adults with CF (3,4) and primary ciliary dyskinesia (5). Whether this also holds true for children aged below 6 years, and which outcome to use preferentially during clinical follow-up and as study endpoint, is unclear as yet.…”
mentioning
confidence: 99%